The contribution of increased equity to the estimated social benefits from a transfer program: An illustration from PROGRESA/Oportunidades - Alderman, Harold; Behrman, Jere R.; Tasneem, Afia (Oxford University Press, 2019)
Most impact evaluations of Conditional Cash Transfers (CCTs) and Unconditional Cash Transfers (UCTs) focus on the returns to increased human capital investments that will be reaped largely or exclusively in the future (e.g., when current children have increased productivities as adults). But the objectives of these programs are not only to increase human capital investments with implications for future levels and distributions of income but also to alleviate current poverty and reduce current inequality. The current distributional gains from such programs depend on the degree of inequality aversion in the social welfare function. Simulations show that, for a range of inequality aversion parameters, the welfare gains from current redistribution for the Mexican PROGRESA CCT program can be as large, or possibly much larger, than the estimated present discounted value of future earnings from human capital investments in lower and upper secondary schooling. These, moreover, are underestimates of the gains from redistribution because, in addition to current gains, such gains will be augmented in the future through the distribution of the returns on the human capital investments induced by cash transfer programs. Therefore, to fully evaluate such programs, it is critical to incorporate the distributional gains, not only the impacts on human capital investments.